Alternatives to Conventional Antibiotics in the Era of Antimicrobial Resistance. Issue 4 (April 2019) - Ghosh, Chandradhish; Sarkar, Paramita; Issa, Rahaf; Haldar, Jayanta
Abstract : As more antibiotics are rendered ineffective by drug-resistant bacteria, focus must be shifted towards alternative therapies for treating infections. Although several alternatives already exist in nature, the challenge is to implement them in clinical use. Advancements within biotechnology, genetic engineering, and synthetic chemistry have opened up new avenues towards the search for therapies that can substitute for antibiotics. This review provides an introduction to the various promising approaches that have been adopted in this regard. Whilst the use of bacteriophages and antibodies has been partly implemented, other promising strategies, such as probiotics, lysins, and antimicrobial peptides, are in various stages of development. Propitious concepts such as genetically modified phages, antibacterial oligonucleotides, and CRISPR-Cas9 are also discussed. Highlights: As bacteria grow resistant to conventional antibiotics, alternatives are being investigated, including antibodies, probiotics, bacteriophages, and antimicrobial peptides currently undergoing clinical trials. The specificity of antibodies, and the inability of bacteria to develop resistance against them, make antibodies attractive, albeit expensive, alternative therapeutic agents. Bacteriophages have been used for therapy in some parts of the world. Antimicrobial peptides have long been considered as potential replacements for antibiotics but with limited success. Synthetic peptides and synthetic membrane-active agents might herald a shift. Probiotics and fecal transplant therapy are already in practice for enhancing the human microbiota. The use of oligonucleotides for silencing resistance genes and resensitizing resistant bacteria to antibiotics is still in the research stage.